Origami inspired deployable structures: Future mobile healthcare for low resource settings - Md Haseen Akhtar; Janakarajan Ramkumar (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
Deployable structures may be defined as systems that can be packed, stored, transported, and then deployed or assembled into functional configurations. The potential applications of deployable structures includes portable or modular buildings, scaffolding, bridges for construction sites and stages for events, spacecrafts with deployable solar panels, antennas, etc, tent systems for disaster relief shelters, and medical equipment such as collapsible hospital beds, examinations tables. The literature suggests many more applications but there is a gap of how to achieve such systems from a design perspective. This study takes deployable mobile clinics as an example to delve deep into the product design, development and deployment inspired by the ancient art of origami.